2017
DOI: 10.2147/opth.s142167
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of corneal collagen cross-linking for keratoconus on the ocular higher-order aberrations

Abstract: BackgroundCorneal collagen cross-linking (CXL) is the only treatment currently available to arrest the progression of keratoconus. The procedure consists of photopolymerization of stromal collagen fibers induced by combined action of a photosensitizing substance (riboflavin or vitamin B2) and ultraviolet-A light.PurposeTo determine changes in the ocular higher-order aberrations (HOAs) after CXL and its correlation with changes in visual acuity.DesignProspective interventional study.Subjects and methodsThis stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(33 reference statements)
4
3
0
Order By: Relevance
“…In this work, we recorded the corneal thickness before and after the procedure. Statistically significant corneal thinning was found after the procedure as reported by many other previous studies 23,29. This thinning can be explained by postoperative keratocyte apoptosis and structural changes in corneal collagen fibrils and extracellular matrix in the anterior stroma.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this work, we recorded the corneal thickness before and after the procedure. Statistically significant corneal thinning was found after the procedure as reported by many other previous studies 23,29. This thinning can be explained by postoperative keratocyte apoptosis and structural changes in corneal collagen fibrils and extracellular matrix in the anterior stroma.…”
Section: Discussionsupporting
confidence: 82%
“…These results are relatively different from the results found by El-Massry et al who found that total HOAs and total coma were significantly reduced at 6 months by 25% and 18%, respectively. Significant improvement was seen in spherical aberration by 8.71%, while no significant change was observed in trefoil 23. As stated before, the main changes in HOAs after corneal cross-linking were in the coma, particularly vertical coma, and spherical aberrations.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This prompted us to investigate in our series a possible correlation between an improvement in corneal aberrations and corrected visual acuity, as previously reported by El-Massry et al [ 19 ]. If such an association was detected, one could have concluded that improved corneal aberrations, more than topographical flattening, would play a significant role in improving CDVA in the long term after CXL.…”
Section: Discussionsupporting
confidence: 53%
“…It should be considered that the i-Trace aberrometer was previously shown to be valid for characterizing ocular aberrations in keratoconus. 30,31 All measurements with the TMS-4, Pentacam, ORA and i-Trace were taken by the same experienced and qualified technician to avoid any bias.…”
Section: Methodsmentioning
confidence: 99%